Electric Power Quality - Chattopadhyay, Surajit; Mitra, Madhuchhanda; Sengupta, Samarjit; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
In the present day deregulated power market electric power quality issues have become great concerns of utilities, end users and manufacturers. Worldwide researches are going on to address those issues. Electric Power Quality has evolved from the researches carried out by the authors.
1 Introduction -- 2 Electric Power Quality -- 3 Unbalance -- 4 Harmonics -- 5 Transients -- 6 Sag, Swell, Interruption, Undervoltage and Overvoltage -- 7 DC Offset, Electric Noise, Voltage Fluctuation, Flicker and Power Frequency Variation -- 8 Unbalance Assessment using Sequence Components -- 9 Unbalance Assessment using Feature Pattern Extraction Method -- 10 Useful Tools for Harmonic Assessment -- 11 Harmonic Assessment using FPEM in V-V and I-I Planes -- 12 Clarke and Park Transformation -- 13 Harmonics Assessment by FPEM in Clarke and Park Planes -- 14 Harmonic Assessment by Area Based Technique in V-V and I-I Planes -- 15 Harmonic Assessment by Area Based Technique in Clarke and Park Planes -- 16 Assessment of Power Components by FPEM and ABT -- 17 Transients Analysis -- 18 Passivity and Activity Based Model of Polyphase System.
Keywords: Engineering; Production of electric energy or power; Electric engineering; Engineering; Power Electronics, Electrical Machines and Networks; Energy Technology